2020
DOI: 10.1097/01.aoa.0000652860.14694.38
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Analgesia in Labor: The VRAIL Pilot Study—A Preliminary Randomized Controlled Trial Suggesting Benefit of Immersive Virtual Reality Analgesia in Unmedicated Laboring Women

Abstract: (Anesth Analg. 2019;128(6):e93–e96) Pain management during childbirth has long been the focus of many researchers in the anesthesiology field, as an estimated 60% of laboring women receive neuraxial analgesia for their pain. Because epidural analgesia can have multiple side effects, some women elect to have an unmedicated birth either independently or with medical therapies. One option for unmedicated labor assistance is immersive virtual reality (VR) distraction to provide a pleasant environment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(101 citation statements)
references
References 0 publications
7
89
0
5
Order By: Relevance
“…Similar to other relevant studies, the women experienced no side effects (Ebrahimian & Rahmani Bilandi, 2020; Frey et al, 2019). Preferring nonpharmacological methods that have no side effects considering the patient safety and that are inexpensive such as VR will increase the patient satisfaction and the quality of healthcare services.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Similar to other relevant studies, the women experienced no side effects (Ebrahimian & Rahmani Bilandi, 2020; Frey et al, 2019). Preferring nonpharmacological methods that have no side effects considering the patient safety and that are inexpensive such as VR will increase the patient satisfaction and the quality of healthcare services.…”
Section: Discussionsupporting
confidence: 86%
“…The study revealed that VR reduced the perceived pain level of the pregnant woman when dilatation was 9 cm. Wong et al (2020) Similarly, the randomised controlled studies by Frey et al (2019) showed that using VR during labour reduced pain. JahaniShoorab et al (2015) also determined that women who used VR in episiotomy repair experienced less pain.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations